Perbandingan pendidikan Cina dan pendidikan India era British di Tanah Melayu - Ariffin Khairi, Kamaruddin Mohd Kamal, Jusoh Adnan (N/A, 2014)
Perbandingan pendidikan Cina dan pendidikan India era British di Tanah Melayu by Ariffin Khairi, Kamaruddin Mohd Kamal, Jusoh Adnan,